ACTIVIDADES LÚDICAS PARA DESARROLLAR LA EXPRESIÓN ORAL, EN LOS NIÑOS DE CUARTO AÑO DE EDUCACIÓN BÁSICA, PARALELO “A” EN LA UNIDAD EDUCATIVA “VIGOTSKY”, RIOBAMBA – CHIMBORAZO, PERIODO 2018-2019 - Cuji Real, Vanesa Estefania (2020)
The present investigative work with the theme LEISURE ACTIVITIES TO DEVELOP ORAL EXPRESSION, IN CHILDREN OF FOURTH YEAR OF BASIC EDUCATION, PARALLEL “A” IN THE EDUCATIONAL UNIT “VIGOTSKY”, RIOBAMBA - CHIMBORAZO, PERIOD 2018-2019.” It is to determine the importance of recreational activities and how it affects the development of oral expression. Being that the variables used in this research, it presented through the compilation of information obtained from books, magazines, websites among others, using a methodology with an inductive, deductive and analytical approach, because the questions applied were values numerical that allow us to examine the data analysis, the correspondence between variables, framed in the educational sciences. The design used was non-experimental, so there was no manipulation of the variables, evidenced by the observation sheet. We worked with three types of research, the field research applied to the 26 students of the Fourth Year, parallel "A", of the Educational Unit "Vigotsky", the descriptive or explanatory research obtained a general idea of the problem, in exploratory research, the different problems encountered were recognized, such as fear of expressing oneself easily. Finally, it concluded that, investigating the great variety of recreational activities, are beneficial, both for us and future professors and for our students, allowing us to use, employ and favor in different areas and subjects, contributing great advantages when communicating.